2019
DOI: 10.1111/hepr.13304
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sodium glucose cotransporter 2 inhibitor on histological features and glucose metabolism of non‐alcoholic fatty liver disease complicated by diabetes mellitus

Abstract: Aim The aim of this study was to investigate the therapeutic potential of sodium glucose cotransporter 2 inhibitor (SGLT2I) as an effective therapeutic option for non‐alcoholic fatty liver disease (NAFLD). Methods In this prospective study, nine patients with NAFLD complicated by type 2 diabetes mellitus (DM), were introduced to the regimen of canagliflozin 100 mg once daily for 24 weeks and were evaluated by liver histology at pretreatment and at 24 weeks after the start of treatment. The primary outcome was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
87
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 37 publications
8
87
1
2
Order By: Relevance
“…However, the number of participants with fibrosis or severe fibrosis was small, which affects the interpretability of these results. Extending recent data demonstrating the individual effects of GLP‐1RAs or SGLT2 inhibitors on NAFLD, the present results are the first to demonstrate the effect of this combination in reducing NAFLD biomarkers in people with type 2 diabetes, and indicate that combining these two agents may exert stronger beneficial effects on NAFLD than each drug alone. Moreover, as NAFLD is independently associated with cardiovascular disease, and the cardiovascular benefits of GLP‐1RAs and SGLT2 inhibitors are now well established, the EXE once weekly + DAPA combination may confer a reduction in cardiovascular risk in patients with type 2 diabetes and NAFLD.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…However, the number of participants with fibrosis or severe fibrosis was small, which affects the interpretability of these results. Extending recent data demonstrating the individual effects of GLP‐1RAs or SGLT2 inhibitors on NAFLD, the present results are the first to demonstrate the effect of this combination in reducing NAFLD biomarkers in people with type 2 diabetes, and indicate that combining these two agents may exert stronger beneficial effects on NAFLD than each drug alone. Moreover, as NAFLD is independently associated with cardiovascular disease, and the cardiovascular benefits of GLP‐1RAs and SGLT2 inhibitors are now well established, the EXE once weekly + DAPA combination may confer a reduction in cardiovascular risk in patients with type 2 diabetes and NAFLD.…”
Section: Discussionsupporting
confidence: 73%
“…With regard to SGLT2 inhibitors, a 24‐week, open‐label, randomized trial of dapagliflozin (DAPA) monotherapy in patients with type 2 diabetes and NAFLD reported overall improvements in hepatic steatosis, along with attenuation of fibrosis in a subset of patients with significant fibrosis . Additionally, 24 weeks of canagliflozin treatment demonstrated improvements in the individual histological components of NASH (eg, steatosis, lobular inflammation and ballooning) in patients with type 2 diabetes and NAFLD . Building on these results, the GLP‐1RA and SGLT2 inhibitor combination could have a synergistic effect on improving steatosis, steatohepatitis and/or fibrosis in patients with type 2 diabetes and NAFLD; however, this remains to be examined in a randomized controlled trial.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…At present there are only small uncontrolled studies reporting anecdotal benefits to liver histology with SGLT2 inhibitors with improvement that is somewhat beyond what would be expected from the modest 2%‐3% weight loss. Whether this is an indication of weight‐independent mechanisms of action remains to be established.…”
Section: The Future Of Treating Nash In Patients With T2dmmentioning
confidence: 96%